Autogenic Relaxation with Audiomusic Instrumental Media on Pain Scale in Post Sectio Caesarea Patients - Dian Ayu Ningsih Ismi; Aprina Aprina; Purwati Purwati (Jurnal Kesehatan)
Injuries to the abdominal wall and uterus cause pain by severing nerve fibers and also by pressure on the joints. One method of pain management is autogenic relaxation therapy with instrumental audiomusic media. The purpose of this study was to determine the effect of autogenic relaxation with instrumental audiomusic media on pain scales in postcesarean section patients at RSUD Dr. H. Abdul Moeloek Lampung Province This study used a quantitative approach with a one group pretest-posttest pre-experimental design. The time of the study was February-March 2023. The population in this study were post sectio caesarea patients. The sampling method in this study was to use accidental sampling technique and obtained a sample of 32 respondents. The instrument used to measure the pain scale uses a Numerical Rating Scale (NRS) and an observation sheet that records the pain scale before and after the procedure. Statistical tests used the Wilcoxon signed rank test. The results of the study obtained an average decrease in pain scale from 7.28 to 6.21 before and after the intervention. So that a p value of 0.000 (p value